Microfoundations of strategic management: Toward micro–macro research in the resource-based theory - José Francisco Molina Azorín (BRQ Business Research Quarterly, 2014)
Over the last few years, a new stream of research has emerged in the field of strategic management which focuses on the analysis of its microfoundations. This line of research analyzes strategic topics examining their foundations rooted in individual actions and interactions. The main purpose of this paper is to examine this emerging literature of microfoundations, indicating its usefulness and main characteristics. Through a systematic literature review, this paper contributes to the field by identifying the main areas studied, the benefits and potential of this approach, and some limitations and criticisms. Moreover, the paper studies how the integration of micro and macro aspects in strategy research may be carried out, examining several works that use a multilevel approach. Some methodological approaches that may help to effect this integration are indicated. These aspects will be analyzed in relation to the resource-based theory."
Keywords: 650; Strategic management; Microfoundations; Resource-based theory; Multilevel research; Micro–macro integration